Process simulation of hydrogen production through biomass gasification: introduction of torrefaction pre-treatment - Yong, Yung Sheng; Ruwaida, Abdul Rasid (Elsevier Ltd, 2021)
Torrefaction is a pretreatment method that converts biomass to a fuel-like substance that can replace coal for sustainable power generation. In this work, a thermodynamic-based process simulation model was developed to simulate the gasification of empty fruit bunch (EFB), with torrefaction as pretreatment, to determine the optimum conditions; equivalence ratio, reactor temperature, torrefaction medium concentration, steam-to-biomass (S/B) ratio and system configuration were studied to determine their influence on hydrogen concentration, higher heating value (HHV), syngas ratio and cold gas efficiency (CGE). The highest hydrogen yield was obtained at an S/B ratio of 1.3 at 800 C, with a syngas ratio of 2.5 and a CGE of 84%. Concentration of torrefaction medium showed no effect on hydrogen concentration due to the simplicity of the model used, but work is in progress in this direction. Therefore, steam gasification is more suitable than air gasification in hydrogen production.